Neutrophil to Hemoglobin Lymphocyte Ratio (NHLR) as a Novel Biomarker is Superior to Neutrophil Lymphocyte Ratio (NLR) and Platelet Lymphocyte Ratio (PLR) as Predictors of Advanced Colorectal Cancer - Purnomo, Heri; Handaya, Yuda; Setyawan, Nurcahya (Indonesian Journal of Cancer, 2024)
Background: Neutrophils, Hemoglobin, and Lymphocytes are biological markers that may be related to the colorectal cancer stage. Neutrophils to Hemoglobin-Lymphocytes Ratio (NHLR) is a new biomarker that will be tested with Neutrophil Lymphocyte Ratio (NLR) and Platelet Lymphocyte Ratio (PLR) as common biomarkers that have been shown to have predictive value with colorectal cancer stage. This study aims to prove NHLR as a new biomarker that can predict advanced colorectal cancer in terms of staging and site of cancer compared to NLR and PLR. Methods: This is a retrospective cross-sectional study. Data obtained from the medical records of colorectal cancer patients undergoing surgery at Dr Sardjito Hospital from 2020 until 2022. Results: 386 patients enrolled in the study, and 62 patients met the inclusion criteria. Twentyeight patients (45.16 %) were male, and 34 (54.84 %) were female. The mean age is 58.82 years. Bivariate analysis showed a significant relationship between NHLR, NLR, and PLR with colorectal cancer stage and significant differences between NHLR and NLR with early and advanced colorectal cancer, but not with PLR. There are also significant differences between NHLR, NLR, and PLR with colorectal cancer sites in the colon and rectum. Still, in locally advanced stages of colorectal cancer, there is no significant association between NLR and cancer sites. On the contrary, there are significant differences between colon and rectal cancer sites with NHLR and PLR. Conclusions: NHLR is superior to NLR and PLR in predicting the stage and site of advanced colorectal cancer.